ANALISIS MANAJEMEN TRANSPORTASI MENGGUNAKAN METODE VOGEL’S APPROXIMATION (VAM) DAN METODE MODIFIED DISTRIBUTION (MODI) - Angguni Reanty; Sarwani .; Hendro Waryanto (Universitas Pamulang, 2015)
TRANSPORTATION MANAGEMENT ANALYSIS USING VOGEL'S APPROXIMA-TION (VAM) AND METHOD OF DISTRIBUTION MODIFIED (MODI). This study aimed to analyze the problems of transportation, especially the problem transportation costs by using Vogel's Approximation (VAM) and modified distribution method (MODI). In this study VAM methods used to find the initial solution and then proceed with the search for the optimal solution by using MODI. The data obtained is data derived from PT.Pilar Inkasari Karya - East Jakarta on shipment per month for 3 years ie 2011 to 2013. The analysis showed that the optimization of the burden of transportation costs Rp 2.225.288.000 annually is obtained by using initial solution Vogel's Approximation method (VAM) and final solution to the Modified method Distribution (MODI). From these results it can be concluded that the method of Vogel's Approximation (VAM) and modified distribution method (MODI) can be used to solve the problem of transportation. Keywords : Vogel’s Approximation Method. Modified Distribution Method